Investor Behavioral Bias and Mutual Fund Investment Decisions: Implications for Culturally Sensitive Investor Education in Indonesia - Yusnita, Rita Tri; Nugraha, Nugraha; Disman, Disman; Sari, Maya; Aminullah, Zakariya Pamuji (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study examines the effect of behavioral bias on mutual fund investment decisions in Indonesia by positioning attitude toward risk as a mediating variable and cultural orientation as a moderating variable, with implications for culturally sensitive investor education. Methods: A quantitative causal–explanatory design was employed using primary data from a survey of 300 individual mutual fund investors selected through purposive sampling. Data were analyzed using Confirmatory Factor Analysis and Hayes PROCESS macro Model 15 in SPSS to test direct, indirect, and moderated relationships among behavioral bias, attitude toward risk, cultural orientation, and investment decisions. Results: Behavioral bias significantly influences investment decisions both directly and indirectly through attitude toward risk. Cultural orientation moderates these relationships by weakening bias-driven effects under stronger cultural orientations, confirming a moderated–mediated model integrating psychological and sociocultural determinants of investment behavior. Novelty: This study offers a novel integrative framework combining behavioral finance and cultural finance perspectives while explicitly linking them to investor education. It highlights how behavioral bias, risk attitude, and cultural orientation should inform the design of culturally sensitive financial literacy and advisory strategies, providing an evidence-based foundation for developing investor education programs that address behavioral and cultural factors in mutual fund decision-making.